1999
DOI: 10.1099/0022-1317-80-2-307
|View full text |Cite
|
Sign up to set email alerts
|

North American and European porcine reproductive and respiratory syndrome viruses differ in non-structural protein coding regions.

Abstract: Although North American and European serotypes of porcine reproductive and respiratory syndrome virus (PRRSV) are recognized, only the genome of the European Lelystad strain (LV) has been sequenced completely. Here, the genome of the pathogenic North American PRRSV isolate 16244B has been sequenced and compared with LV. The genomic organization of 16244B was the same as LV but with only 63n4 % nucleotide identity. The 189 nucleotide 5h non-coding region (NCR) of 16244B was distinct from the LV NCR, with good c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
307
2
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(314 citation statements)
references
References 60 publications
3
307
2
2
Order By: Relevance
“…A chymotrypsin-like (3C-like) cysteine protease domain resides at the N-terminal end of NSP2 (16). NSP2 has been shown to be variable in length among sequenced isolates of arteriviruses (1,36,39,61). PRRSV type 1 strain LV NSP2 is 861 aa in length while type 2 strains have an additional 100 aa or more, and lactate dehydrogenase-elevating virus and EAV encode NSP2 proteins which are 733 and 401 aa in length, respectively (1,20,36,82,85).…”
Section: Amino Acid Alterations In Europrrsv Nsp1␤ and Nsp2mentioning
confidence: 99%
See 1 more Smart Citation
“…A chymotrypsin-like (3C-like) cysteine protease domain resides at the N-terminal end of NSP2 (16). NSP2 has been shown to be variable in length among sequenced isolates of arteriviruses (1,36,39,61). PRRSV type 1 strain LV NSP2 is 861 aa in length while type 2 strains have an additional 100 aa or more, and lactate dehydrogenase-elevating virus and EAV encode NSP2 proteins which are 733 and 401 aa in length, respectively (1,20,36,82,85).…”
Section: Amino Acid Alterations In Europrrsv Nsp1␤ and Nsp2mentioning
confidence: 99%
“…NSP2 has been shown to be variable in length among sequenced isolates of arteriviruses (1,36,39,61). PRRSV type 1 strain LV NSP2 is 861 aa in length while type 2 strains have an additional 100 aa or more, and lactate dehydrogenase-elevating virus and EAV encode NSP2 proteins which are 733 and 401 aa in length, respectively (1,20,36,82,85). Snijder et al (66) found that the NSP2 protein of EAV was involved in proteolysis of replicase precursors and membrane association of the virus replication complex, but no confirming work has been reported for other arteriviruses.…”
Section: Amino Acid Alterations In Europrrsv Nsp1␤ and Nsp2mentioning
confidence: 99%
“…The strain used for challenge was PRRSV 16244B, which was isolated in February 1997 from a case of porcine reproductive failure in Johnson County, Nebraska. 1 The inoculum was prepared after three passages in MARC-145 cells. Six gilts were inoculated intranasally with 1 ml of PRRSV (me-dian tissue culture infective dose ϭ 10 7 /ml), which was delivered in two aliquots of 0.5 ml per nostril.…”
Section: Experimental Designmentioning
confidence: 99%
“…The genotypes have a similar genomic organization, and 10 open reading frames (ORFs) have been identifi ed (1)(2)(3). Nonstructural protein 2 (Nsp2) and ORF5 are the most variable regions (4,5), coding for replicase protein and neutralizing epitope, respectively.…”
mentioning
confidence: 99%